PENINGKATAN KEMAMPUAN MEMBACA DAN MENULIS MELALUI BIMBINGAN BELAJAR GRATIS BAGI SISWA KELAS 1 DAN 2 DI SD NEGERI 040457 BERASTAGI - Mariana Surbakti; Breti A. Sembiring; Elda Sihaloho; Jelita Karo Sekali; Nova Uli Simbolon; Sarah Tarigan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Community service activities are one of the mandatory subjects contained in the MBKM curriculum at HKBP Nommensen University, Medan and must be taken by every student. In this activity, each participant carries out these activities in an area adjacent to the student's residence. This activity lasts for a month and is carried out after finishing school hours at each school. Free tutoring activities are carried out with the aim of teaching students to be able to overcome the problem of decreased interest in learning and the low ability of students in reading and writing due to the lengthy online learning process due to the Covid-19 pandemic. All activity participants and students carry out the learning process by applying the applicable health protocols. Our team conducts PKM activities at SD Negeri 040457 Berastagi from February 2, 2022 to February 26, 2022, every Tuesday to Saturday for one and a half hours. The learning process is carried out with guidance in small classes and using learning media such as letter lists, animal pictures, fairy tale books, etc. that can attract students' interest. The results of the activity showed an increase in students' interest in learning and reading and writing skills by up to 70%. This proves that students can be more enthusiastic about learning if there is direct assistance and interaction.